Comparative Relationship of E-Commerce Growth versus Trade (Indonesian and Singapore Case Studies) - Wardani, Pina; Nurbaiti, Nurbaiti; Dharma, Budi (Universitas Ibn Khladun Bogor, 2023)
The rapid development of technology is driving every human being to continue to innovate, one of which is in terms of shopping or trading to make it easier and faster. E-commerce has become one of the solutions to solving the issue of efficiency in doing sale-purchase transactions. The research is comparative to the qualitative approach with the data model used is SWOT, but since each SWOT component is not so clear then the literature study approach is used to define SWOT. The data used is e-commerce approach data from 2017 – 2022. E-commerce has a positive and beneficial effect on trade in both the States of Indonesia and Singapore, because with the increase of e-commerce in the two States then the value of transactions income through the trade sector has become and increased the rate of economic growth has become better in the respective countries.